Identifying novel biomarkers through data mining—A realistic scenario?. Issue 3 (12th January 2015) - Griss, Johannes; Perez‐Riverol, Yasset; Hermjakob, Henning; Vizcaíno, Juan Antonio
Abstract : In this article we discuss the requirements to use data mining of published proteomics datasets to assist proteomics‐based biomarker discovery, the use of external data integration to solve the issue of inadequate small sample sizes and finally, we try to estimate the probability that new biomarkers will be identified through data mining alone.